Monitoramento do treinamento auditivo e da funcionalidade em criança com Transtorno do Processamento Auditivo Central - Garcia, Elisandra Santos Mendes (2022)
Central Auditory Processing refers to the efficiency and effectiveness with which the central nervous system uses auditory information. Changes in the functionality of the Central Auditory Nervous System lead to Auditory Processing Disorder (CAPD). CAPD involves the auditory system and is characterized by a persistent limitation in the performance of auditory activities with significant consequences for participation. The intervention process proposed for CAPD is called Auditory Training (AT) as a set of conditions and/or tasks designed to activate the auditory system and associated systems. The present study considers strong associations between the central auditory nervous system and functionality, in terms of participation, capacity and occupational performance. Its bases were anchored in the theoretical logic of the biopsychosocial model and in the International Classification of Functioning, Disability and Health (ICF). The objective of this research was to evaluate the effects of an auditory training program on the functionality of a child with CAPD. It was also aimed to develop, apply and analyze an auditory training program for a child with CAPD; create an instrument to monitor the functionality of a child with CAPD, submitted to auditory training, analyze the changes in its implementation from the participant's perspective; and, to analyze the perception of the effects of auditory training on functionality, from the perspective of the child, the mother and the teacher. Therefore, a pre-experimental, intra-subject case study with an A-B design was chosen. Audiological and CAP assessments were performed and, based on the diagnosis of CAPD, a program of ten sessions of auditory training was developed. To analyze functionality issues, the Canadian Occupational Performance Measure (COPM) was applied. A Functionality Monitoring instrument was created, applied in four stages of the study, to measure changes during the intervention, named MFTAI. After completion of the intervention program, the auditory assessment and auditory processing were reapplied, in addition to the COPM. The child's mother answered the anamnesis and the Pediatric Evaluation of Disability Inventory (PEDI) and a teacher answered the PEDI, also before and after the AT. The results obtained in this thesis demonstrate that the intervention process promoted an improvement in the scores in all tests of the CAP assessment battery, but the CAPD is still characterized. The scores of the MFTAI instrument, the aspects of functionality anchored in the biopsychosocial model and ICF, as well as the occupational performance based on the COPM, allowed us to affirm that the TA promoted positive changes, inferring a progressive improvement in the children's personal perceptions regarding their functions and structures of the body (related or not to auditory processing) and improvement in activities and participation, regarding the components of Behavior, Auditory Skills and Activities and Occupations. The mother's and the teacher's perception complement each other in order to assess the positive changes in functionality and dialogue with each other in order to corroborate the limitations in the child's participation. It is concluded that from the design used and, subject to its limitations, and with the use of measures, it is possible to affirm that the Auditory Training caused positive effects on the functionality of a child with Central Auditory Processing Disorder. For future research, we suggest replicating the study with a larger sample of participants and intra-subject quasi-experimental designs to verify the possibility of generalizing the data found. Added to this, it is suggested to improve the MFTAI instrument, in the psychometric perspective, created in this thesis to measure changes during the intervention.